At Westonci.ca, we provide reliable answers to your questions from a community of experts. Start exploring today! Experience the ease of finding quick and accurate answers to your questions from professionals on our platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
To solve the equation [tex]\(5x + 2 = 3x + 4(2x - 1)\)[/tex] for [tex]\(x\)[/tex], we will go through the following steps:
Step 1: Distribute the 4 on the right side
First, distribute the 4 to both terms inside the parentheses:
[tex]\[ 5x + 2 = 3x + 4(2x) - 4(1) \][/tex]
Simplify the terms:
[tex]\[ 5x + 2 = 3x + 8x - 4 \][/tex]
Step 2: Combine like terms on the right side
Next, combine the [tex]\(3x\)[/tex] and [tex]\(8x\)[/tex] on the right side:
[tex]\[ 5x + 2 = 11x - 4 \][/tex]
Step 3: Move all terms involving [tex]\(x\)[/tex] to one side and constants to the other
To isolate [tex]\(x\)[/tex], we move all terms involving [tex]\(x\)[/tex] to one side of the equation and all constants to the other side. Start by subtracting [tex]\(11x\)[/tex] from both sides:
[tex]\[ 5x - 11x + 2 = -4 \][/tex]
Simplify the equation:
[tex]\[ -6x + 2 = -4 \][/tex]
Next, move the constant term 2 to the other side by subtracting 2 from both sides:
[tex]\[ -6x + 2 - 2 = -4 - 2 \][/tex]
Simplify the equation:
[tex]\[ -6x = -6 \][/tex]
Step 4: Solve for [tex]\(x\)[/tex]
Finally, solve for [tex]\(x\)[/tex] by dividing both sides of the equation by [tex]\(-6\)[/tex]:
[tex]\[ x = \frac{-6}{-6} \][/tex]
Simplify the result:
[tex]\[ x = 1 \][/tex]
Thus, the solution to the equation [tex]\(5x + 2 = 3x + 4(2x - 1)\)[/tex] is [tex]\(x = 1\)[/tex].
Step 1: Distribute the 4 on the right side
First, distribute the 4 to both terms inside the parentheses:
[tex]\[ 5x + 2 = 3x + 4(2x) - 4(1) \][/tex]
Simplify the terms:
[tex]\[ 5x + 2 = 3x + 8x - 4 \][/tex]
Step 2: Combine like terms on the right side
Next, combine the [tex]\(3x\)[/tex] and [tex]\(8x\)[/tex] on the right side:
[tex]\[ 5x + 2 = 11x - 4 \][/tex]
Step 3: Move all terms involving [tex]\(x\)[/tex] to one side and constants to the other
To isolate [tex]\(x\)[/tex], we move all terms involving [tex]\(x\)[/tex] to one side of the equation and all constants to the other side. Start by subtracting [tex]\(11x\)[/tex] from both sides:
[tex]\[ 5x - 11x + 2 = -4 \][/tex]
Simplify the equation:
[tex]\[ -6x + 2 = -4 \][/tex]
Next, move the constant term 2 to the other side by subtracting 2 from both sides:
[tex]\[ -6x + 2 - 2 = -4 - 2 \][/tex]
Simplify the equation:
[tex]\[ -6x = -6 \][/tex]
Step 4: Solve for [tex]\(x\)[/tex]
Finally, solve for [tex]\(x\)[/tex] by dividing both sides of the equation by [tex]\(-6\)[/tex]:
[tex]\[ x = \frac{-6}{-6} \][/tex]
Simplify the result:
[tex]\[ x = 1 \][/tex]
Thus, the solution to the equation [tex]\(5x + 2 = 3x + 4(2x - 1)\)[/tex] is [tex]\(x = 1\)[/tex].
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.